D-band broadening drives pollutant oxidative polymerization for intermediate-free water purification - Jiajun Lu; Rongjie Jiang; Defang Ma; Baoyu Gao; Shuang Zhao; Yan Wang (Water Research, 2026)

Chronic ammonia-N exposure impairs the intestinal health of the Siberian sturgeon (Acipenser baerii Brandt): through the pathways of oxidative stress, tight junction proteins, inflammatory factors, and intestinal microbiota - Huimin Sun; Qiang Hu; Yujie Huang; Siqi Zhao; Guangwei Cao; Zhizhen Zhang; Fei Wang; Defang Chen; Zhiqiong Li; Xin Zhang (Fish & Shellfish Immunology, 2026)

Degradation of p-Nitrophenol (PNP) via photocatalytic ozonation using perylene diimide polymer - Defang Liu; Chao Wang; Zhuo Cheng; Qiyao Zhao; Xuelian Zeng; Chiyu Wen; Jing Zhao; Guoxiang Zhu; Jun Wang; Yongfa Zhu (Chemical Engineering Journal, 2026)

Genetically engineered MSC vesicles encapsulated with dual-gene siRNAs integrated peptide dendrimer nanoplatform for rheumatoid arthritis treatment - Min Nie; Danqing Huang; Defang Meng; Xuanqi Liu; Yuanjin Zhao; Lingyun Sun (Chemical Engineering Journal, 2025)

hUC-MSCs exosomes-loaded hydrogels for systemic lupus erythematosus wound treatment - Defang Meng; Danqing Huang; Xiaoquan Wei; Min Nie; Xiulan Zheng; Yuanjin Zhao; Lingyun Sun (Chemical Engineering Journal, 2025)

Silencing LINC01547 induces hepatocellular carcinoma cell apoptosis and metastasis inhibition via the ADAR1/FAK and miR-146b-5p/RAC1 axes - Dan Wang; Huijie Zhao; Ying Zhao; Xuejing An; Chuanqin Shi; Zhaohai Pan; Qiusheng Zheng; Xin Wang; Jun Lu; Defang Li (Apoptosis, 2025)

Recycling and high-value utilization of polyethylene terephthalate wastes: A review - Tianxiang Ren; Haihua Zhan; Huaizhong Xu; Lifeng Chen; Wei Shen; Yudong Xu; Defang Zhao; Yuanyi Shao; Yongtao Wang (Environmental Research, 2024)

Sialic acid catabolism contributes to Vibrio mimicus virulence - Ruoxuan Zhao; Zhenyang Qin; Yang Feng; Yi Geng; Xiaoli Huang; Ping Ouyang; Defang Chen; Hongrui Guo; Huidan Deng; Jing Fang; Weimin Lai (Aquaculture, 2023)

Spatial allocation model of ecological land in the urban fringe of Xi’an City based on geosynclinal fold belt structure - Defang Zhao (Arabian Journal of Geosciences, 2020)

Characterization, tissue distribution of resistin gene and the effect of fasting and refeeding on resistin mRNA expression in Siberian sturgeon ( Acipenser baerii ) - Ni Tang; Yanlin Liu; Zhengzhi Tian; Shaoqi Xu; Mei Wang; Hu Chen; Bin Wang; Ya Li; Yan Wang; Song Yang; Liulan Zhao; Defang Chen; et al. (Journal of Fish Biology, 2020)
Resistin as an adipokine identified from rodents in 2001 is involved in many biological processes. However, little is known about this gene in fish. We cloned Siberian sturgeon ( Acipenser baerii ) resistin cDNA of 795 base pairs, encoding 107 amino acids, which showed 38–40% identity to human and rodents. Real‐time quantitative PCR showed that the resistin gene was widely distributed in tissues of Siberian sturgeon, with the highest expression in liver. After fasting for 1, 3, 6 and 10 days, the expression of the resistin gene in the liver of Siberian sturgeon decreased significantly, and after refeeding on the 10 days of fasting the resistin mRNA expression increased rapidly, suggesting that resistin may play an important role in liver in response to starvation. Taken together, these results suggest that resistin may be involved in the regulation of energy homeostasis in liver.

Physiological responses and tolerance of flax (Linum usitatissimum L.) to lead stress - Gen Pan; Lining Zhao; Jianjun Li; Siqi Huang; Huijuan Tang; Li Chang; Zhigang Dai; Anguo Chen; Defang Li; Zheng Li; Yong Deng (Acta Physiologiae Plantarum, 2020)

Genome-wide development of simple sequence repeats database for flax (Linum usitatissimum L.) and its use for genetic diversity assessment - Gen Pan; Anguo Chen; Jianjun Li; Siqi Huang; Huijuan Tang; Li Chang; Lining Zhao; Defang Li (Genetic Resources and Crop Evolution, 2020)

GSK3β inhibition suppresses the hepatic lipid accumulation in Schizothorax prenanti - Yan Wang; Xiaochen Zhan; Wei Luo; Liulan Zhao; Song Yang; Defang Chen; Zhiqiong Li; Linjie Wang (Fish Physiology and Biochemistry, 2019)

Identification and characterization of the RCI2 gene family in maize (Zea mays) - YANG ZHAO; HAIQING TONG; RONGHAO CAI; XIAOJIAN PENG; XIAOYU LI; DEFANG GAN; SUWEN ZHU (Journal of Genetics, 2014)

Identification and expression analysis of primary auxin-responsive Aux/IAA gene family in cucumber (Cucumis sativus) - DEFANG GAN; DAN ZHUANG; FEI DING; ZHENZHOU YU; YANG ZHAO (Journal of Genetics, 2013)

Genome-wide analysis of BURP domain-containing genes in Maize and Sorghum - Defang Gan; Haiyang Jiang; Jiao Zhang; Yang Zhao; Suwen Zhu; Beijiu Cheng (Molecular Biology Reports, 2011)